Linking Promise to the Podium - Talent Identification and Development (TID) in New Zealand - A Report to SPARC`s Board from the TID Taskforce - Scott, R. (2004)
Successful talent identification consists of three aspects: extensive knowledge of the performance demands within a particular sport; an accurate assessment of athlete capabilities in relation to these demands; and the ability to predict future performance levels based on current athlete's characteristics1. The first two points have been well researched with many countries currently basing their identification models on them. Point three, however, is problematic especially considering the long-term nature of athlete development. The multi-dimensional nature of talent, its dependency on genetics, environment, encouragement and its effect on an individual's physical and psychological traits makes it difficult to establish a strategy that is accurate in its predictive ability. There is no simple solution anywhere to this complex problem of long-term talent identification. To deduce otherwise fails to acknowledge the multi-faceted nature of talent and that its development relies on many influences (e.g. biomechanical, physiological, physical, psychological and environmental factors). This was the overall conclusion reached by the Taskforce. If a world champion is an aggregate product of genetic endowment, a supportive environment and highly specialised training, it seems naïve to direct our efforts towards just identifying talent; talent development, which commences when a child is born, is the crucial but often misunderstood link. It is contended that the New Zealand TID strategy prioritise the establishment of a systematic and holistic long-term development process, with an on-going identification strategy embedded in it. Over an extended period of time, indicators of potential can be identified, enhanced and monitored so that the more indicators an individual has or gains, the higher the probability of potential sporting success. And herein lies the challenge - talent development involves more people than the coach, for parents, schools, physical education, sports, providers, education agencies and clubs all need to work cohesively to ensure each athlete, irrespective of their genetics, is given every opportunity to succeed. Such a collaborative approach is the only way forward for our "talented" athletes to fulfil their potential. The opportunity for SPARC to lead this process cannot be overstated. Success at the elite level will not come overnight but will be as a result of a sustained long-term effort over many years. The Taskforce believes the fruits borne from this strategy will not be seen until 2016 and its ramifications will challenge the way athletes are developed in this country.